2018
DOI: 10.5713/ajas.16.0139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four dim vs high intensity red color light regimens on growth performance and welfare of broilers

Abstract: ObjectiveBroilers show clear preference towards red color light (RL). However setting of an optimum light intensity is difficult since dim intensities that favor growth reduce welfare. This experiment was conducted to test the most effective RL intensity regimen (Dim [5 lux; DI] vs high [320 lux; HI]) in combination applied at different growth stages that favors for both performance and welfare.MethodsComplete randomize design was adopted with 6 replicates. Treatments were; T1 = early DI (8–21 d)+latter HI (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This strain has several commercial impressions on poultry markets and has a unique growth rate and yielding ability characteristics compared to other available strains [12]. Therefore, rare studies had been performed to evaluate the effect of different lighting programs and comparing with continuous programs to obtain the best growth performance by reducing the drawbacks of high growth rate, feed consumption and considering maintaining the immune system in maximum growth on broilers [13].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…This strain has several commercial impressions on poultry markets and has a unique growth rate and yielding ability characteristics compared to other available strains [12]. Therefore, rare studies had been performed to evaluate the effect of different lighting programs and comparing with continuous programs to obtain the best growth performance by reducing the drawbacks of high growth rate, feed consumption and considering maintaining the immune system in maximum growth on broilers [13].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…As shown in table 10, little is known on the preference of broiler chickens for certain light colours. It seems that broilers show a preference towards red colour light (Senaratna, et al, 2018), which may be explained by the increased levels of activity found when birds are exposed to red light at different periods or throughout the entire rearing period. Nevertheless, colour preference tests have been hardly applied in experiments where lighting parameters were investigated in broilers.…”
Section: Table 10mentioning
confidence: 99%
“…Nevertheless, colour preference tests have been hardly applied in experiments where lighting parameters were investigated in broilers. Next to that, setting of an optimum light intensity is difficult since dim intensities that favour growth reduce welfare (Senaratna, et al, 2018). Thus, studies where colour preferences are tested are needed, and when possible, also in combination with the testing of most effective intensity schedules that favours both performance and welfare in broiler chickens.…”
Section: Table 10mentioning
confidence: 99%